ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA KOPERASI KREDIT JAYAKARTA ENDE - Soka, Efrem Alfredo Ringgi; Banda, Falentina Lucia; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2023)
The purpose of this study was to analyze the sources and uses of working capital at the Jayakarta Ende Cooperative Credit. The type of research used in this research is to use quantitative methods with data collection techniques (1) observation, (2) interviews, (3) documentation, (4) library research. The data analyzed is in the form of financial reports, namely the balance sheet of the Jayakarta Ende Credit Cooperative for 2018–2020. Financial report data were analyzed using analysis techniques of sources and use of working capital. The sources of working capital for the Jayakarta Ende Cooperative Credit in 2018 and 2019 consist of: Reducing the CS Program, Increasing Principal Savings, Compulsory Savings, Swakarsa Savings. And for 2019 and 2020 the sources of working capital consist of: Reduction in Buildings, Computers and Print, CS Program, Increase in Principal Savings, Compulsory Savings, Independent Savings, and Special Reserve Funds. While the use of working capital for the Jayakarta Ende Credit Cooperative in 2018 and 2019 consists of: building additions, building depreciation, computer and pint depreciation, CS program depreciation, and reserve funds. And for 2019 and 2020 the use of working capital consists of: Increased Depreciation of Buildings, Depreciation of Computers and Print, Depreciation of the CS Program, and Reduction in Reserve Funds.